2005
DOI: 10.1002/ijc.21270
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐specificity phosphatase 1 and serum/glucocorticoid‐regulated kinase are downregulated in prostate cancer

Abstract: Inactivation of tumor suppressor genes through deletion, mutation and epigenetic silencing has been shown to occur in cancer. In our study, we combined DNA demethylation and histone deacetylation inhibition treatments with suppression subtraction hybridization (SSH) and cDNA microarrays to identify potentially epigenetically downregulated genes in PC-3 prostate cancer cell line. We found 11 genes whose expression was upregulated after relieving epigenetic regulation. Expression of 3 genes [dual-specificity pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 39 publications
10
44
4
Order By: Relevance
“…A low expression of DUSP1 has been observed in ovarian and prostate cancer (56,57). Moreover, in line with our study, Tomioka et al (58) observed a low expression of this gene in head and neck cancer.…”
Section: Discussionsupporting
confidence: 91%
“…A low expression of DUSP1 has been observed in ovarian and prostate cancer (56,57). Moreover, in line with our study, Tomioka et al (58) observed a low expression of this gene in head and neck cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Although much effort has focused on the molecular interactions modulating DUSP1 activity in mammalian cell lines, little is known about the role of DUSP1 in carcinogenesis. DUSP1 inactivation is frequent in prostate and urothelial tumors (16,17), and recent observations indicate that immunohistochemical positivity for DUSP1 in human HCC is associated with longer patients' survival (18). However, the interactions of DUSP1 with ERK and the SKP2/CKS1 ligase and the mechanisms responsible for DUSP1 inactivation in the liver and other tumors have not been analyzed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a later study showed DUSP1 mRNA expression to be lower in hormone-refractory prostate carcinomas than in benign prostate hyperplasia (BPH) or untreated prostate carcinomas. Higher DUSP1 protein levels were found in BPH, normal prostate and high-grade prostate intraepithelial neoplasia (Rauhala et al, 2005). Consistent with the low levels of DUSP1 in response to androgen ablation, DUSP1 mRNA was found to be upregulated upon androgen treatment of LNCaP cells (Arnoldussen et al, 2008) The androgen receptor (AR) has been identified as responsible for increased expression of DUSP1 (and several other DUSPs) upon interaction with testosterone.…”
Section: Role In Prostate Cancermentioning
confidence: 90%
“…Consistent with the low levels of DUSP1 in response to androgen ablation, DUSP1 mRNA was found to be upregulated upon androgen treatment of LNCaP cells (Arnoldussen et al, 2008) The androgen receptor (AR) has been identified as responsible for increased expression of DUSP1 (and several other DUSPs) upon interaction with testosterone. However, DUSP1 implication in prostate cancer is not yet fully resolved, since there have been reports showing that both high and low levels of DUSP1 may have an antiapoptotic effect, depending on which MAP kinase DUSP1 is targeting (Rauhala et al, 2005). Similarly, androgens protect LNCaP cells from 12-O-tetradecanoylphorbol-13-acetate-and thapsigargin-induced apoptosis via down-regulation of JNK activity through an increase in DUSP3 expression.…”
Section: Role In Prostate Cancermentioning
confidence: 99%